Development of polymyxin- and aminoglycoside-based outer membrane permeabilizers: a review - Ramirez, Danzel Marie; Schweizer, Frank (Frontiers in Microbiology, 2025)
The prevalence of antimicrobial resistance (AMR) necessitates the development of alternative therapeutic options, particularly against critical priority Gram-negative pathogens. The utilization of antibiotic adjuvants or potentiators is an advantageous strategy that targets bacterial resistance mechanisms, thereby augmenting the activity of an antibiotic used in combination. Among these, outer membrane (OM) permeabilizers are a promising class of adjuvants which compromise the OM barrier unique to Gram-negative bacteria. This review focuses on the emerging role of polymyxins and aminoglycosides – two structurally distinct antibiotics with different modes of action, but share the ability to interact with the bacterial OM. Here, we explore the design, modification, and application of polymyxin- and aminoglycoside-based OM permeabilizers, highlighting their potential against resistant Gram-negative infections.